2016
DOI: 10.1016/j.vetpar.2016.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different light sources for trapping Culicoides biting midges, mosquitoes and other dipterans

Abstract: 2 Highlights -Biting nematocerans and mosquitoes showed a clear affinity to specific wavelenghts, being fluorescent light sources more efficient than incandescent and LED lights.-Proven vectors of important economically diseases such as Culicoides obsoletus/C. scoticus are highly attracted to traps fitted with ultraviolete (UV) and green LEDs.-The paper highlighted the potential use of traps equipped with light sources emitting in wavelenghts close to 570 nm (green colour). Wavelengths in green (570 nm) result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 34 publications
(21 reference statements)
1
28
1
Order By: Relevance
“…In comparison to UV light, incandescent light traps captured both fewer species of biting midges and lower numbers of C. obsoletus females. A similar difference has also been demonstrated through comparative studies conducted in South Africa (Venter and Hermanides 2006), Spain (del Río et al 2013, González et al 2016) and in the US (Anderson and Linhares 1989, Wieser‐Schimpf et al 1990). Despite UV light being the most widely used tool for biting midge surveillance, the ecological mechanism through which light of different wavelengths attracts Culicoides to traps remains poorly understood (Carpenter et al 2008).…”
Section: Discussionsupporting
confidence: 59%
“…In comparison to UV light, incandescent light traps captured both fewer species of biting midges and lower numbers of C. obsoletus females. A similar difference has also been demonstrated through comparative studies conducted in South Africa (Venter and Hermanides 2006), Spain (del Río et al 2013, González et al 2016) and in the US (Anderson and Linhares 1989, Wieser‐Schimpf et al 1990). Despite UV light being the most widely used tool for biting midge surveillance, the ecological mechanism through which light of different wavelengths attracts Culicoides to traps remains poorly understood (Carpenter et al 2008).…”
Section: Discussionsupporting
confidence: 59%
“…Culicoides obsoletus (Meigen) and Culicoides scoticus Downes and Kettle, by contrast, responded randomly to every colour of LED used with the exception of red, which was less attractive to all species (Hope et al ., ). Overall, LED traps collected fewer Culicoides than the Centers for Disease Control (CDC) UV light suction trap (Hope et al ., ; González et al ., ) or other commercially available domestic light sources (Wakefield et al ., ). Harrup et al .…”
Section: Discussionmentioning
confidence: 99%
“…Studies evaluating the use of various colours of light have been conducted in Australian (Bishop et al ., , ), South American (Silva et al ., ), Indian (Harrup et al ., ) and European (Hope et al ., ; González et al ., ) Culicoides species. Although these studies demonstrated attraction specifically to UV, blue and green light, they also suggested that particular Culicoides species may react differently to various light colours.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, CDC traps were set throughout the study area during 2016 and 2017. We used traps with UV light as they are recommended to attract Culicoides [ 54 ]. Moreover, since this study is part of a broader one aimed at studying the community of dipteran vectors, we also used incandescent light traps.…”
Section: Methodsmentioning
confidence: 99%